2004
DOI: 10.1111/j.1460-9568.2004.03715.x
|View full text |Cite
|
Sign up to set email alerts
|

A soluble Nogo receptor differentially affects plasticity of spinally projecting axons

Abstract: In the central nervous system, regeneration of injured axons and sprouting of intact axons are suppressed by myelin-derived molecules that bind to the Nogo receptor (NgR). We used a soluble form of the NgR (sNgR), constructed as an IgG of the human NgR extracellular domain, to manipulate plasticity of uninjured primary afferent and descending monoaminergic projections to the rat spinal cord following dorsal rhizotomy. Rats with quadruple dorsal rhizotomies were treated with intrathecal sNgR or saline, or were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 62 publications
(86 reference statements)
2
29
0
Order By: Relevance
“…31,32 In order to prevent observer bias, all sections were coded in order to blind the analysis. Each photomicrograph was captured using Northern Eclipse software (Empix Neuroimaging, version 6.0) and was thresholded using an edge-detecting algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In order to prevent observer bias, all sections were coded in order to blind the analysis. Each photomicrograph was captured using Northern Eclipse software (Empix Neuroimaging, version 6.0) and was thresholded using an edge-detecting algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…A computerized program provided average density measurements for each 20-mm segment of the 720-mm long rectangular strip. To quantify CGRP-positive axon density in the spinal cord, we carried an automated thresholding procedure, 31,33,34 which first defines the thickest and brightest regions, and then, following application of a Laplacian omnidirectional edge-detection filter, the finer processes ( Figure 1, bottom). The edge-detection filter effectively normalizes the signal-to-noise ratio such that small variations in immunoreactivity across sections are eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…C7/8 DRI produced a consistent deafferentation gap in laminas III-IV of the C7 dorsal horn. Densitometric analyses of VGLUT1-and CTB-positive terminals were performed within the deafferentation gap, by measuring terminal density as a function of depth in the dorsal horn (Ramer et al, 2001MacDermid et al, 2004;Scott et al, 2005). After C7/8 DRI, the density of both VGLUT1-and CTB-labeled terminals was decreased but remained unchanged for at least 20 d postoperatively.…”
Section: C7/8 Dri Produces a Stable Deafferentation Gap In The Dorsalmentioning
confidence: 99%
“…Quantitative analyses of terminal density in the dorsal horn were performed by measuring terminal density as a function of depth in the dorsal horn, as we have done previously (Ramer et al, 2001MacDermid et al, 2004;Scott et al, 2005). Densitometric analyses of vesicular glutamate transporter 1 (VGLUT1)-and CTB-positive terminals were performed within the consistent deafferentation gap apparent in C7 after C7/8 DRI.…”
Section: Tissue Processing and Image Analysismentioning
confidence: 99%
“…51,52 Another antagonist, NgREcto, is a soluble, truncated form of NgR, which has been shown to alleviate inhibition of both Nogo and myelin in vitro (Fournier et al, 2002). Recent work from our group examines the effects of NgR activity using a different form of soluble NgR in vivo; 53 in these experiments, we found that NgR antagonism augmented rhizotomy-induced sprouting of both descending monoaminergic axons and peptidgeric primary afferents in the cervical dorsal horn. The discovery of an anti-NgR monoclonal antibody, capable of inhibiting binding of Nogo, MAG, and OMgp, and of blocking inhibition of myelin in vitro, has now been reported.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 94%